PELATIHAN PENGGUNAAN E-COMMERCE DAN PROMOSI MENGGUNAKAN MEDIA SOSIAL UNTUK MENINGKATKAN PENJUALAN PADA KOMUNITAS UMKM BUNDO KANDUANG: Training on the Use of E-Commerce and Promotion Using Social Media to Increase Sales in the Bundo Kanduang MSME Community - Ellbert Hutabri; Weni Lestari Putri; Nanda Jarti (ASOSIASI IDEBAHASA KEPRI, 2023)
The mothers of the Bundo Kanduang MSME community are an association of mothers who have businesses in the Tiban area of ??Batam City, this community was founded in 2019 with the aim of increasing friendship between mothers who have businesses that are run offline or online such as selling through live streaming Facebook or on the buying and selling forum (FJB) Batam City group. During this time the activities carried out are in the form of recitations which are carried out routinely once a month. Based on the results of observations made, several problems were found in the buying and selling process of this community, such as 1) limited number of audiences watching, 2) market limitations, because it is only for Batam city residents, 3) low level of trust from potential buyers, 4) intense competition tightness and delivery, and other issues. Based on the problems above, e-commerce training is provided and how to promote its products so that there is an increase in consumers. The training is given using the guided discovery method, which is a learning method based on the participants' experiences, then the presenters provide a solution, namely using e-commerce, resulting in an account that can be used to sell. After one month of observing the e-commerce that had been made, it was found that there were several products that experienced a significant increase in sales, namely balado chips and parfume.